2013
DOI: 10.1016/j.neuroimage.2013.02.034
|View full text |Cite
|
Sign up to set email alerts
|

The radial diffusivity and magnetization transfer pool size ratio are sensitive markers for demyelination in a rat model of type III multiple sclerosis (MS) lesions

Abstract: Determining biophysical sensitivity and specificity of quantitative magnetic resonance imaging is essential to develop effective imaging metrics of neurodegeneration. Among these metrics apparent pool size ratio (PSR) from quantitative magnetization transfer (qMT) imaging and radial diffusivity (RD) from diffusion tensor imaging (DTI) are both known to relate to histological measure of myelin density and integrity. However their relative sensitivities towards quantitative myelin detection are unknown. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
95
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 39 publications
(47 reference statements)
11
95
1
Order By: Relevance
“…Our results are consistent with other literature which reports decreased FA values in the fornix with age [37,38]. While studies have shown that age-independent demyelination or axonal injury strongly correlates with specific DTI metrics such as RD or AD, respectively [39,40,41], it is unsurprising to see changes in FA, AD and RD in our current study sample given that multiple events involving different aspects of white matter integrity are involved in aging.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other literature which reports decreased FA values in the fornix with age [37,38]. While studies have shown that age-independent demyelination or axonal injury strongly correlates with specific DTI metrics such as RD or AD, respectively [39,40,41], it is unsurprising to see changes in FA, AD and RD in our current study sample given that multiple events involving different aspects of white matter integrity are involved in aging.…”
Section: Discussionsupporting
confidence: 93%
“…1,23,24 A relatively high MPF and its correlation with GA in the thalamus are also in concordance with early myelination of this structure commencing at the 25th week. 25 While the myelin content provides the main determinant of the MPF in WM according to our results and other studies, [6][7][8][9][10] subtle effects of other tissue properties on this parameter are also discernible. An increased MPF in the germinal matrix observed in young fetuses suggests that unmyelinated brain tissue creates a low-signal background highlighting fine distinctions in the macromolecular content not related to myelin and probably associated with cellularity.…”
Section: Discussionsupporting
confidence: 83%
“…A limited capability of both lesion volume and MPF in lesions to explain clinical status supports the current understanding of MS as a whole-brain disease in which widespread microscopic demyelination in normal-appearing tissues mainly determines progression of disability (17,28). A decrease of MPF in all brain tissues is generally consistent with progressive demyelination as the primary pathologic substrate of neural tissue damage in MS (17) and strong associations between MPF and myelin content established in animal models (4,5,(12)(13)(14)(15)(16). While microscopic myelin damage is probably the dominant cause of MPF reduction in normal-appearing WM, pathologic changes of MPF in MS lesions may also be driven by edema associated with inflammation because an increase in water content causes dilution of the total macromolecular concentration.…”
Section: Discussionmentioning
confidence: 65%
“…Practical interest in MPF as a prospective biomarker in MS is driven by a number of recent animal studies (4,5,(12)(13)(14)(15)(16) that demonstrated strong relationships between MPF and myelin. MPF has been highly positively correlated with histologic measurements of myelin density in animal models, including both normal brain tissues and demyelination (4,12,15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation